Studi Tentang Manfaat Perumusan Ancaman Pidana Mati dalam Beberapa Kualifikasi Tindak Pidana Berat - Putuhena, Janes Julian (Lembaga Intelektual Muda Maluku, 2024)
This study aims to determine the benefits of the formulation of the death penalty threat in several qualifications for serious crimes. The type of writing used in this writing is normative juridical writing using a statute approach. This type of writing is descriptive and analytical. The main sources of data for this research are the 1945 Constitution, Law No. 15 of 2003, Law No. 8 of 1981, and Court Decisions. Data analysis was carried out qualitatively. The findings of this study are that terrorist crimes, narcotics, and psychotropics are threatened with high and severe penalties with the possibility of the maximum sentence of the defendant, namely the death penalty in addition to imprisonment and fines. Considering that terrorist crimes, narcotics, and psychotropics are included in special types of criminal acts, criminal threats against them can be imposed cumulatively by imposing 2 types of main crimes at once. In the Criminal Code, the imposition of two main sentences at once is not possible so that no punishment is imposed in the form of imprisonment and a fine because the Criminal Code only requires one of the main crimes. However, as a special criminal act, for narcotics and psychotropic crimes, the judge is allowed to sentence the defendant with two main crimes at once, which are generally in the form of the death penalty, life sentence or prison sentence with the aim that the punishment burdens the perpetrator so that the crime can be tackled in the community